1989
DOI: 10.1111/j.1365-2230.1989.tb00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Naevoid hypertrichosis-report of a patient with multiple lesions

Abstract: Naevoid hypertrichosis is an unusual congenital disorder consisting of a solitary circumscribed area of terminal hair growth which is not associated with any other systemic abnormalities. We describe a patient with multiple areas of circumscribed naevoid hypertrichosis on the trunk and limbs who also had lipodystrophy at some affected sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Localized areas of hypertrichosis can be seen in congenital pigmented nevi, Becker's nevus, overlying a neurofibroma, scrotal hair, 1188 hairy pinnae, hairy elbows (OMIM 139600), 1178,1189 anterior and posterior cervical hypertrichosis (OMIM 239840), 1178,1190,1191 nevoid hypertrichosis, 1192,1193 spinal dysraphism ('faun-tail'), 1194,1195 ectopic cilia, 1196 and in depigmented hypertrichosis following Blaschko's lines. 1197 Nevoid hypertrichosis is a congenital circumscribed patch of terminal hair without other abnormalities.…”
Section: Congenital Circumscribed Hypertrichosis 1171mentioning
confidence: 99%
“…Localized areas of hypertrichosis can be seen in congenital pigmented nevi, Becker's nevus, overlying a neurofibroma, scrotal hair, 1188 hairy pinnae, hairy elbows (OMIM 139600), 1178,1189 anterior and posterior cervical hypertrichosis (OMIM 239840), 1178,1190,1191 nevoid hypertrichosis, 1192,1193 spinal dysraphism ('faun-tail'), 1194,1195 ectopic cilia, 1196 and in depigmented hypertrichosis following Blaschko's lines. 1197 Nevoid hypertrichosis is a congenital circumscribed patch of terminal hair without other abnormalities.…”
Section: Congenital Circumscribed Hypertrichosis 1171mentioning
confidence: 99%
“…[8] However, they mentioned partial lipoatrophy or bony abnormalities as reported in the literature. [910] Further, a review of the literature by us revealed that NH may be associated with ocular, cerebral, mental, myoskeletal, neurological, gastrointestinal, pulmonary and facial dysmorphia [Table 1]. Patients with NH must be investigated to rule out any systemic involvement associated with the skin lesion(s).…”
Section: Discussionmentioning
confidence: 99%
“…X-linked hypertrichosis causes symmetrical marked hypertrichosis in males and there may be patchy involvement in females, but this is unlikely to be the explanation in our patient and the case of Flannery et al [19891 because it does not interfere with growth or development. In nevoid hypertrichosis there are patches of hypertrichosis in a swirled distribution, but in addition there are areas of lipodystrophy and multiple congenital abnormalities [Cox et al, 1989;Rogers, 19911. Although facial asymmetry can be associated with severe torticollis, this is unlikely to explain the proposita's asymmetry because her torticollis was mild enough to resolve spontaneously without the development of plagiocephaly. The patient of Flannery et al [19891 and our proposita appear to be more similar to each other than to patients with hypertrichosis cubiti.…”
Section: Discussionmentioning
confidence: 99%